PENERAPAN HUKUM PROGRESIF DALAM PERKARA PIDANA DI BIDANG NARKOTIKA - Indrawati Indrawati (Jurnal Cakrawala Hukum, 2017)
Narcotics abuse has become a necessity in the modern world. Law No. 35 of 2009 on Narcotics is strictly regulated on what actions can be categorized as criminal offenses and what sanctions will be faced by those legally and convincingly proven to be the perpetrators of narcotics abuse. In the past 5 years, the government has massively enforced law enforcement and law enforcement in the field of narcotics and has sent dozens of people to challenge death against firing squads in the execution process. Fidelis a civil servant from Sanggau West Kalimantan, was arrested by the BNN apparatus for being proven to plant marijuana at his home. Through a process integrated in the Indonesian criminal justice system, the judge finally ruled that Fidelis was legally and convincingly guilty and sentenced to 8 months in jail plus a fine of 1 billion 1-month subsidence cage. Many parties admit it because Fidelis should be tried and punished, but many also praise the courage of the judge who has decided the case by using the attachment of progressive legal theory.DOI: https://doi.org/10.26905/idjch.v8i2.2117